Using intervention mapping (IM) to develop a self-management programme for employees with a chronic disease in the Netherlands - Heerkens Yvonne F; Engels Josephine A; van der Gulden Joost WJ; Detaille Sarah I; van Dijk Frank JH (BMC, 2010)
Abstract Background Employees with a chronic disease often encounter problems at work because of their chronic disease. The current paper describes the development of a self-management programme based on the Chronic Disease Self-Management programme (CDSMP) of Stanford University to help employees with a chronic somatic disease cope with these problems at work. The objective of this article is to present the systematic development and content of this programme. Methods The method of intervention mapping (Bartholomew 2006) was used to tailor the original CDSMP for employees with a chronic somatic disease. This paper describes the process of adjusting the CDSMP for this target group. A needs assessment has been carried out by a literature review and qualitative focus groups with employees with a chronic disease and involved health professionals. On the basis of the needs assessment, the relevant determinants of self-management behaviour at work have been identified for the target population and the objectives of the training have been formulated. Furthermore, techniques have been chosen to influence self-management and the determinants of behaviour and a programme plan has been developed. Results The intervention was designed to address general personal factors such as lifestyle, disease-related factors (for example coping with the disease) and work-related personal factors (such as self-efficacy at work). The course consists of six sessions of each two and a half hour and intents to increase the self management and empowerment of employees with a chronic somatic disease. Conclusion Intervention mapping has been found to be a useful tool for tailoring in a systematic way the original CDSMP for employees with a chronic somatic disease. It might be valuable to use IM for the development or adjusting of interventions in occupational health care.